2007
DOI: 10.1111/j.1399-3062.2006.00184.x
|View full text |Cite
|
Sign up to set email alerts
|

Invasive adenoviral infections in T‐cell‐depleted allogeneic hematopoietic stem cell transplantation: high mortality in the era of cidofovir

Abstract: Mortality rates of ADV pneumonitis after allogeneic HSCT remain high in the era of cidofovir. Clinical trials are needed to evaluate management strategies for this life-threatening infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
114
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(118 citation statements)
references
References 19 publications
(24 reference statements)
4
114
0
Order By: Relevance
“…29,[31][32][33] However, the observations made at our and other institutions indicate that initiation of antiviral treatment at the time of first detection of viremia may not prevent progression to severe AdV disease in many instances, and that earlier initiation of preemptive treatment could therefore be beneficial. 1,7,11,21,30,[33][34][35][36] Adenoviruses are known to persist in epithelial cells and lymphoid tissue, and AdV infections occurring during the posttransplant period appear to result from virus reactivation in most instances. Our observations revealed that virtually all patients who experienced systemic AdV infection had the virus detectable in serial stool specimens, with or without clinical symptoms of enteritis, before the onset of viremia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…29,[31][32][33] However, the observations made at our and other institutions indicate that initiation of antiviral treatment at the time of first detection of viremia may not prevent progression to severe AdV disease in many instances, and that earlier initiation of preemptive treatment could therefore be beneficial. 1,7,11,21,30,[33][34][35][36] Adenoviruses are known to persist in epithelial cells and lymphoid tissue, and AdV infections occurring during the posttransplant period appear to result from virus reactivation in most instances. Our observations revealed that virtually all patients who experienced systemic AdV infection had the virus detectable in serial stool specimens, with or without clinical symptoms of enteritis, before the onset of viremia.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although molecular detection of viremia was shown to precede the onset of clinical symptoms of disseminated viral disease, preemptive antiviral treatment with virustatic agents such as cidofovir, ribavirin or foscarnet administered at first detection of the virus in PB failed to prevent lethal outcome of AdV disease in most instances. 1,11,17,18 It has been shown that the adoptive transfer of donor-derived AdV-specific T-lymphocytes may provide an attractive treatment option in patients with invasive AdV infection, but the favorable outcome observed upon in vivo expansion of the transferred T cells appeared to be related to the early onset of adoptive T-cell transfer during the course of infection. 19,20 These observations suggested that timely initiation of antiviral treatment, possibly before the occurrence of invasive infection, might be beneficial.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Disseminated adenovirus (Ad) infection is among the most lethal post-HPCT complications, especially in paediatric patients (Flomenberg et al, 1994). The importance of T-cell immunity in preventing Ad infection is evidenced by higher disease incidence associated with targeted T cell-specific treatment for graft versus host disease (GVHD) (La Rosa et al, 2001) and in recipients of T cell-depleted grafts, where T-cell recovery may be delayed (Chakrabarti et al, 2002;Symeonidis et al, 2007). Antiviral agents, including cidofovir and ribavirin, may be effective in reducing viral loads in patients with at least partial T-cell immunity, but have been less effective in the absence of viral immunity, indicating the need for alternative therapies (Feuchtinger et al, 2007;Lenaerts et al, 2008;Neofytos et al, 2007).…”
Section: Introductionmentioning
confidence: 99%